2002
DOI: 10.1136/ard.61.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal pain is more generalised among people from ethnic minorities than among white people in Greater Manchester

Abstract: Objective: To assess the prevalence of musculoskeletal symptoms among the major ethnic minority populations of Greater Manchester. Method: The study group was a community sample of 2117 adults from the Indian, Pakistani, Bangladeshi, and African Caribbean communities. Questionnaires administered by post and by an interviewer were used to assess the presence of any musculoskeletal pain, pain in specific joints, and the level of physical function. Ethnicity was self assigned. The results were compared with those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 16 publications
9
58
4
Order By: Relevance
“…The high prevalence of musculoskeletal must be a concern for health educators as this could have a delirious effect on their health and that providing early support and preventive measures are necessary for a better physical health of students. Some of the differences in the high prevalence of musculoskeletal pains reported in this study compared to other studies are difficult to explain but this could be attributed to the cultural patterns in which students from different countries report musculoskeletal problems, with students downplaying the prevalence in some countries and in other countries students may more likely complain (Allison et al, 2002). What we cannot determine is whether these musculoskeletal effects are lifetime or episodic, as reporting musculoskeletal pains do not necessarily mean that the pains are continuous.…”
Section: Discussioncontrasting
confidence: 50%
“…The high prevalence of musculoskeletal must be a concern for health educators as this could have a delirious effect on their health and that providing early support and preventive measures are necessary for a better physical health of students. Some of the differences in the high prevalence of musculoskeletal pains reported in this study compared to other studies are difficult to explain but this could be attributed to the cultural patterns in which students from different countries report musculoskeletal problems, with students downplaying the prevalence in some countries and in other countries students may more likely complain (Allison et al, 2002). What we cannot determine is whether these musculoskeletal effects are lifetime or episodic, as reporting musculoskeletal pains do not necessarily mean that the pains are continuous.…”
Section: Discussioncontrasting
confidence: 50%
“…A further study focusing on people from ethnic minorities has now been conducted in Tameside and inner city Manchester. 28 In conclusion, this study provides generalizable estimates of back and neck pain prevalence stratified into various categories of severity. We have demonstrated that BMI is an important independent predictor of back pain and its severity, and that deprivation is an important predictor of disabling back pain.…”
Section: Discussionmentioning
confidence: 99%
“…Our questions also were similar to those used in several European population-based studies, conducted by mail and telephone interviews, on the prevalence of chronic pain (Allison et al 2002;Croft et al 1993;Macfarlane et al 2001;Papageorgiou et al 2002;Smith et al 2001). …”
Section: Chronic Widespread Painmentioning
confidence: 99%